An Experimental Investigation of Combustion Emissions and Diesel Engine Performance of Water in Diesel Nano Emulsion Fuel - Hamadi, Adel Sharif; Dhahad, Hayder Abed; Khudhur, Ali Ghufran (Journal of Petroleum Research and Studies, 2018)
Water in Diesel Nano-Emulsions (WiDNE) fuel are an important environmental fuels for decreasing the combustion pollution of diesel engines. WiDNE fuel is a dispersion stable thermodynamic and kinetic system consisting of diesel oil, surfactant and water phase. WiDNE fuel due to their nano scale droplet size (20–200 nm) and large surface area burns more completely and hence a reduction in emissions than straight diesel. The objective of this project is to evaluate the combustion characteristics of WiDNE fuel prepared by rotor-stator homogenizer using mixed surfactants based on nonionic emulsifiers Span™ 80, Tween™ 80. Direct injection (DI), Fiat engine was used and run at 1500 rpm, constant fuel pressure (400 bar) with varying the operation load. Multi gas analyzer model 4880 was used to measure the concentration of the emission gases such as NOx, unburned total hydrocarbon HC, CO2 and CO. The AVL-415 meter was used for smoke emissions. The experimental results of WiDNE imposes the capability to improve fuel properties, the engine efficiency as well as reduction of gas emissions.